The Legal Responsibility of the Land Office in the Issuance of Certificates of Ownership on Disputed Land - Avina Wafiroh (Semarang State University Undergraduate Law and Society Review, 2025)
Land disputes remain a recurring issue in Indonesia, including in rapidly developing areas such as Bekasi Regency. One case that reflects the complexity of land affairs occurred in Tambun Selatan District, specifically in the Setia Mekar Residence Cluster 2, where residents holding Land Ownership Certificates faced land execution based on a court decision that had obtained permanent legal force. As a result, these residents lost the legal certainty previously guaranteed by their certificates. This study aims to examine the factors that led to the issuance of Land Ownership Certificates on disputed land and to analyze the form of legal responsibility held by the Land Office. The research employs a qualitative approach with a non-doctrinal method. The findings reveal that the primary causes of the issuance of Land Ownweship Certificates on contested land include the Land Office's lack of involvement in the juridical proceedings, the existence of a peace agreement between the disputing parties, and data discrepancies between the Land Office and the court. Nevertheless, if residents feel harmed by such decisions, they still have the right to seek accountability from the Land Office and pursue legal remedies either through an administrative lawsuit to the Administrative Court or through a civil lawsuit based on an unlawful act as regulated under Article 1365 of the Indonesian Civil Code.